Cooperative and mobile manipulation of multiple microscopic objects based on micro-hands and laser-stage control. (December 2018) - Ta, Quang Minh; Cheah, Chien Chern
Abstract: While various techniques have been developed for manipulation of biological cells or micro-objects using optical tweezers, the performance and feasibility of these techniques are mostly dependent on the physical properties of the target objects to be manipulated. In these existing techniques, direct trapping and manipulation of the manipulated objects using laser traps are performed, and therefore, existing techniques for optical manipulation are not capable of coordinating and manipulating various types of objects in the micro-world, including untrappable micro-objects, relatively large micro-objects, and laser sensitive biological cells. In this paper, a cooperative control technique is proposed for coordinative and mobile manipulation of multiple microscopic objects using micro-hands with multiple laser-driven fingertips and robot-assisted stage control. Several virtual micro-hands are formed by coordinating multiple optically trapped micro-particles that serve as the laser-driven fingertips, and then utilized for individual and coordinative manipulation of the target micro-objects. Simultaneously, global transportation of all the grasped target objects is performed by controlling the robot-assisted stage. While it is difficult to design multi-fingered hands in micro-scale due to scaling effect, this paper presents the first result on cooperative and mobile manipulation of multiple micro-objects using multiple micro-hands with laser-driven fingertips and robot-assisted stage control. In this paper, a primary study on repositioning strategy of the laser-driven fingertips is also introduced to allow the fingertips in a grasping formation to be repositioned. Rigorous mathematical formulations and solutions are derived to achieve the control objective, and experimental results are presented to demonstrate the effectiveness of the proposed control technique.